Flipped learning in ESL classrooms - Azmat Ali, Mohammad Musab; Md Yunus, Melor; Hashim, Harwati; Abd Rahman, Siti Fatimah (Penerbit UKM, 2022)
The 21st century brings about unprecedented changes to society and how the education process takes effect in schools. the implementation of digital technology brings about a plethora of strategies and approaches to teaching with the aid of technology. The flipped learning approach is one of these approaches gaining momentum in the education scenario. Due to its students and learning centric nature of execution. This comes at a time when technology is in the very heart of the Malaysian Educational policies, seen in the implementation of the Malaysian Education Blueprint. With this in mind, the is a void in a standard framework in implementing the Flipped learning approach. This book tends to the establishment of a framework for the approach in an ESL context. Thus, providing ESL practitioners and educators a framework in how to implement the Flipped Learning approach effectively. Flipped Learning in ESL Classrooms provides an in-depth discussion of the theoretical background and previous research on the Flipped Learning approach. These discussions lead to the establishment of the constructs of the frameworks for the approach in the ESL context. It is hoped this book will shed light on the practical implications of the approach as well as providing a standard guide for those who wish to implement the approach in the teaching of English in a second language environment.